Transforming a Master of Public Health Program to Address Public Health Practice Needs - Lynn D. Woodhouse, EdD, MEd, MPH, CHES; Alberto C. Cardelle, PhD, MPH; Steven W. Godin, PhD, MPH, CHES; Steven E. Shive, PhD, MPH, MA, CHES; Tonya L. Williams; Elizabeth A. Brensinger, MPH; Adenike C. Bitto, MDDS, DrPH, MPH, CHES (Centers for Disease Control and Prevention, 2005)
The future of the constantly changing public health profession is tied to the development of practice skills through competency-based training. In this article, we describe a program change in the Master of Public Health program at East Stroudsburg University in northeastern Pennsylvania. The first goal of the program transition was to ensure that all program elements included the relevant vision, values, mission, goals, and objectives. The second goal was to use continuous data input and evaluation to incorporate opportunities for flexible assessments. The change process helped the university faculty define the program's vision and fostered an environment of community collaboration that guides training for public health professionals.